AGENT-BASED MODELLING: STATE AND PROSPECTS - Eduard A. Lebedyuk (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
The article describes the current condition of agent modeling – a new direction in imitation modeling, which is very important as a tool of  researching complicated heterogeneous decentralized socio-economic  systems. Key spheres of using agent models were identified and researched, examples of models starting from first attempts of  building them to today’s achievements of science both in Russian and  abroad were provided. By analyzing the current condition of agent  modeling the author discusses existing problems and shows further prospects of developing agent modeling.